Stability and efficiency ofdifferent cropping systems in western Himalayan region - GANGWAR, B; KATYAL, V; ANAND, K V (The Indian Journal of Agricultural Sciences, 2011)
Comparative performance of various crops and cropping systems was evaluated for6 years ( 1994 to 2000 ) at 2 locations (R S Pura and Palampur) of AICRP on Cropping Systems representing western Himalyan region to find out diversification opportunities for predominant cropping systems. In mid high altitude intermediate zone of Jammu, rice (Oryza sativa L .)-wheat [Triticum aestivum L. emend. Fiori & Paol]-sorghum [Sorghum bicolor (L.) Moench] + cowpea fodder [Vigna unguiculata(L)Walp] system was identified to be most productive with rice equivalent yield of 11835 kg/ha/ year, energy production of 1 3788 Kx 1000 calories/ha /year and yield stability of 0.45. The next best sequence was rice-mustard [Brassicajuncea (L) Czernj & Cosson ]-greengram [Phaseolus radiatus (L.) Wilczek] with 11 221 kg/ha/year as rice equivalent yield, yield stability of O.42 ,and highest nutrient use productivity of 30.8 kg grain/kg nutrient applied. These 2 systems were distinctly better than existing rice-wheat offering an opportunity to diversify the existing system. At Palampur representing mid hills sub-humid zone of Himachal Pradesh, the crop sequence involving maize (Zea mays L.)+ soybean (Glycine 111ax L) -wheat-fallow was distinctly better with highest rice equivalent yield of 21 412 kg/ha/year and productivity of 58.6.But energetically, maize- pea--potato was better producing highest energy of 366655 K x ·1000 calories/ha/year, while maize - toria -potato was mbre profitable with highest net return of Rs 36 830/ha/year and profitability of Rs 100.9/ha/day. The water use productivity varied fron112.6.8 to 136.2 kg grain/ha em ofwater and nutrient use productivity varied from 20.0 to 27.5 kg grain! kg ofnutrient used was also better in these 2 systems offering sound base to diversity existing n1aize-wheat system through preferable interruption during rabi. The soil fertility could be maintained in various systems over years through use of recommended doses offertilizers in different crops.